Strategi Komunikasi Krisis BKN terhadap Kecurangan Seleksi Calon Aparatur Sipil Negara Tahun 2021 - Muhammad Arya Raharji Najib (Academic Journal of Da'wa and Communication, 2023)
The selection process for Candidates for Indonesia Civil Servants (CASN), which is followed annually by millions of applicants, has never been without the issue of fraud. The peak occurred in 2021 where the issue of fraud developed and caused a crisis at the BKN as the organizer of the CASN selection. This study aims to analyze the crisis communication strategy implemented by BKN in dealing with this CASN selection fraud crisis. The type of research in this study was qualitative with a case study research type with 4 informants who were BKN crisis management teams using purposive sampling. The results showed that BKN uses 9 stages, namely: Crisis identification, Situation analysis, Communication goals, Audience identification, Determining message content, Selection of media and communication activities, Determination of communicators, Implementation of communication activities, and Evaluation. The findings of this study indicate that the nine stages implemented by BKN are able to handle crises effectively and maintain a positive image of the organization.